IMPLEMENTASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN TEMATIK MUATAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA SISWA KELAS III SD N 01 TENGKLIK KABUPATEN KARANGANYAR - Nadziroh Nadziroh; Chairiyah Chairiyah; Wachid Pratomo (Cerdas Proklamator, 2021)
This article aims to describe: 1) the implementation of character values ​​in PPKn thematic learning, 2) supporting and inhibiting factors in the implementation of character values ​​in PPKn thematic learning, 3) solutions in overcoming the inhibiting factors in the implementation of character values. through thematic learning of PPKn content. This research is a qualitative descriptive study. The research was conducted at SD N 01 Tengklik, Karanganyar Regency. The data sources in this study consisted of third grade teachers and third grade students. Data collection techniques using observation, interviews, and documentation. The validity of the data was tested by increasing persistence and triangulation (source, technique and time). The data analysis technique uses an interactive model, namely data collection (data collection), data reduction (data reduction), data display (data presentation), and conclusion drawing/verification (drawing conclusions). The results of the study show that: 1) the implementation of character values ​​in the thematic learning of PPKn content is carried out by carrying out habituation activities that are routinely carried out every day, integrated character values ​​are religious, nationalist, independent, and mutual cooperation values. 2) The supporting factor in the implementation of these character values ​​is the teacher as an example to instill character values ​​and self-awareness of students to realize character values. The inhibiting factor is the lack of attention from family and community in planting character values. 3) The solution to overcome these obstacles is to invite collaboration between parents or guardians of students and teachers to take part in instilling character values.